The impact of IFRS on accounting quality: an empirical study in China from 2010-2019 - Xu, Yuting (2020)
Abstract Increasingly more nations in Europe with free markets join in the adoption of International Financial Reporting Standards (IFRS) for uniform and high-quality accounting standards. However, countries with different economic, political, and institutional environments are not fully studied. China, the second-largest regulated economy in the world, is worthwhile to be analyzed. Since 2007, all Chinese listed firms adopt IFRS and it is already more than ten years now. This study aims to figure out the accounting quality change after IFRS adoption and compare the difference between the early adoption period (2010-2014) and the later adoption period (2015-2019) of the same 42 listed firms. Using, quantitative method, earnings management is measured by earnings smoothness and small positive earnings. The empirical results illustrate that accounting quality improved with lower earnings management. In addition, the accounting quality of the later adoption period is higher than that of the early adoption period. This study proves that IFRS is relevant to regulated markets and longer adoption of IFRS are recommended for higher accounting quality. Keywords IFRS, IFRS adoption, Accounting quality, earnings smoothness, China